Should brand firms always take pioneering position? - Cong Pan (Osaka University, Institute of Social and Economic Research (ISER), 2015)
This paper discusses brand firms' endogenous timing problem when facing nonbrand firms under quantity competition. We study a market comprising brand and nonbrand products. There exist heterogeneous consumer groups-one group buys only brand products while the other one cares little about the brand. These two consumer groups constitute the high- and low-end markets respectively. The brand firms' moving order is endogenized, whereas the nonbrand firms are restricted to move in a later period. We show that if the low-end market is of an intermediate size, the leader-follower equilibrium outcome occurs, and the follower obtains second mover advantage which diminishes when the number of nonbrand firms increases. These results follow from the fact that each brand firm's best response function has an upward jump if the rival's output exceeds a particular level. Thus, the leader's profit function has a downward jump at some particular point while the follower's profit does not.
Keywords: 330